Design and Development of a Pneumatic Bush Installation Tool for Motorcycle Engine Mounting Production Efficiency - Azzahra Nazwa Asyifa; Yuliarto Joko Sumbogo; Dimas Ardiansyah Halim; Joko Suparno (Multidisciplinary Innovations and Research in Applied Engineering, 2025)
The increasing demand for efficient and precise manufacturing processes in the automotive industry has led to the development of automated assembly systems, including pneumatic-based tools. This study focuses on the design, development, and evaluation of a pneumatic Bush installation tool for motorcycle engine mounting production efficiency. The tool was tested against manual methods (hammer and jack) to compare installation time, accuracy, and defect rates (NG). A quasi-experimental approach was used, involving trial and error testing, prototype validation, and comparative analysis. The results showed that the pneumatic system significantly outperformed the manual method, with an 80% improvement in efficiency—reducing installation time from 120 seconds (manual) to 45 seconds (pneumatic). Additionally, Bush misalignment was reduced from 40% (manual) to 10% (pneumatic), while installation-induced defects dropped from 35% to only 5%. The findings demonstrate that the pneumatic-assisted tool provides more consistent pressure control, improved accuracy, and reduced error rates, making it a superior alternative to manual methods. This study contributes to the advancement of automated assembly technologies in the motorcycle manufacturing industry.